Sedentary versus active behavior in people after stroke. (February 2015) - Galea, Sarah L.; Lee, Mi-Joung; English, Coralie; Ada, Louise
<x content-type="archive" xml:space="preserve">Abstract</x> Background: The detrimental effect of sedentary behavior has been acknowledged and the benefit of interrupting sedentary behavior is being explored. Objectives: The aim of this review was to examine sedentary and active behavior of stroke survivors, how these behaviors are accumulated and to explore energy expenditure to understand how much physical activity is required following stroke. Method: MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and EMBASE were searched for studies involving community-dwelling stroke survivors and healthy adults, and using objective measures of sedentary/active behavior or energy expenditure during active tasks. Data were extracted independently by two reviewers. Results: After being assessed against the inclusion criteria, 12 studies were included. The mean ratio (stroke∶controls) of sitting behavior was 1·2∶1 suggesting that stroke survivors are more sedentary than healthy individuals. The ratio of standing and walking time was 0·7∶1 and steps per day was 0·5∶1 suggesting that stroke survivors are less active than healthy individuals. The ratio of bouts of activity/day was 0·7∶1 suggesting that stroke survivors do not interrupt their sedentary time as often as healthy individuals. The ratio of energy expenditure ranged from 1·1 to 2·5∶1 suggesting that stroke survivors expend more energy than healthy individuals for the same activity. Conclusions: Stroke survivors have less bouts of activity than their age-matched counterparts suggesting that they are at risk of health issues. However, stroke survivors expend more energy for the same activity, and this may go some way toward balancing out their reduced amount of physical activity.